LEGALITY IN THE THEORY OF CRIMINAL PROCEDURAL LAW (Academicia Globe: Inderscience Research, 2022)
The article discusses the concept and essence of legality in the theory of criminal procedure law, the importance, conditions and features of its observance, classifies the subjects of observance of legality.